Serve Dynamics: Applying a Bibliometric Approach in the Kinetics and Kinematics Analysis for Flat and Topspin Serves in Tennis - Kumar, Sunil; Das, Ratna; Bairagi, Kushagra; Singh, Malkhan (Physical Education Theory and Methodology, 2024)
Objectives. The study aimed to completely examine the existing research on the investigation of kinetics and kinematics analysis for flat and topspin serves in tennis, with a special focus on improving performance and reducing injury risks for players. Material and Methods. In order to obtain a comprehensive understanding of the data, Scopus searched three variables in each record: (1) the author’s name, (2) the journal name in which the paper was published, and (3) the total number of citations. Bibliometric analysis was used as part of the analysis. To gain a thorough and accurate comprehension, the data was analyzed and interpreted using a variety of data triangulation techniques. Building distance-based co-occurrence networks for bibliometric analysis and synthesis was carried out using the VOS viewer software. The classification and grouping of the terms derived from titles, abstracts, and keywords were carried out based on their degree of interconnectedness. The terms “Serve Dynamics in Tennis”, “Kinetic Analysis in Tennis serve”, “Kinematic Analysis in Tennis serve”, and “Flat and Topspin serve in Tennis” are frequently used in the study, although their meanings are generally interpreted differently. The search yielded 125 papers and 2807 citations, which were used in the study conducted from 2001 to 2024. Results. The study’s findings revealed the primary authors, countries, and subject areas that contribute to a comprehensive understanding of research patterns, influential studies, authorship dynamics, thematic clusters, and international collaborations in the analysis of the kinetics and kinematics for flat and topspin serves in tennis. Conclusions. The study concludes by consolidating current information and identifying potential avenues for broadening the interdisciplinary scope of tennis serve research.